Investigation of the relationship between intraocular pressure and ultrasonographic examination of anterior and posterior segment of the eye in dogs - Özgür Erkan; Kurtuluş Parlak; Mustafa Arıcan (Eurasian Journal of Veterinary Sciences)
Aim: This study was carried out to determine the relationship between intraocular pressure and the examination of the anterior and posterior segment of the eye in the rapid diagnosis and treatment of acute eye diseases. Materials and Methods: The study materials of different age, race, sex and eye diseases without distinction as only the right eyes of 50 clinically healthy dogs were assessed at Selcuk University Veterinary Faculty, Department of Veterinary Surgery. Distribution of the dogs were Golden (4), Boxer (1), Cocker (1), and Terrier (3), 41 were Kangal hybrids, with a mean age of 3 ± 1 year and a weight average of 28 ± 1 kg. All eye examinations were performed within a certain order. Schirmer test kit was used to measure the quantitative amount of tear secretion. Tonovet was used for intraocular pressure measurement, direct ophthalmoscopic examination and ultrasonographic examinations were also performed. Results: In the correlation analysis show that moderate severity correlation was determined between intraocular pressure and anterior segment depth (medium correlation between 0.4-0.6, r: 0.551) in intra ocular pressure increased (n: 6) group. High correlation was also found between intraocular pressure and anterior segment width (high correlation between 0,6-0,8, r: 0,609). In the present study, it was seen that there was a statistically positive change in the measurements of the anterior and posterior segments in intra ocular pressure. Ultrasound- guided examinations have led to the conclusion that glaucoma can be diagnosed precisely. Conclusions: Eventhough, there is a relationship between intraocular pressure and ultrasonographic changes in the anterior segment, it is suggested to increase the number of cases and to make changes more accurate..